Patient neglect in 21st century health-care institutions: A community health psychology perspective. (January 2014) - Reader, Tom W; Gillespie, Alex; Mannell, Jenevieve
Despite the technological and organisational advances of 21st century health-care systems, care scandals and burgeoning complaints from patients have raised concerns about patient neglect in hospitals. This article reviews the concept of patient neglect and the role of community health psychology in understanding its occurrence. Patient neglect has previously been conceptualised as a problem associated with hospital staff attitudes and behaviours, with regulation and training cited as solutions. Yet, a community health psychology perspective shows that the wider symbolic, material and relational aspects of care are crucial for understanding why patient neglect occurs and for outlining new solutions to augment existing interventions.